Investigation on Suitable Spat Collectiors and Culture Sites for Edible Oyster in the Coast of Bay of Bengal, Bangladesh (Bangladesh Journal of Zoology, 2021)
Potential spat collectors and suitable culture sites were investigated for the development of edible oyster culture from June to December 2019 at three study sites (Moheshkhali, the Jeti of Nuniarchora, and Sonadia) of Cox’s Bazar coast of Bangladesh. Four types of collectors such as oyster shell, earthen pot, kortal (windowpane oyster shell) and tiles were investigated. On site sampling of water quality parameters and number of spats on each collector were done at 15-days interval following standard methods. Results indicated insignificant difference (P > 0.05) in temperature, salinity, dissolved oxygen and pH, while significant difference (P < 0.05) in total dissolved solids, total suspended solids and Chl-a content of the water among the study locations. However, these parameters were in suitable range for growth and spawning of oyster. Results also indicated spat recruitment was significantly influenced by the types of collectors and study locations with significantly (P < 0.05) higher spat were recruited in Tiles. Tiles were also found to facilitate with an advantage of recycling of this collector. The location in interaction with polluting materials such as total dissolved solids and total suspended solids had a significant effect on spat recruitment rate and therefore, Sonadia was the most suitable location for spat recruitment. This study site can also be used as a suitable location for the development of oyster culture in the cost of Bay of Bengal, Bangladesh based on its environmental characteristics.Bangladesh J. Zool. 49 (2): 257-265, 2021